Pilgrimage and Religious Mobilization in Europe - Barbato, Mariano P. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This volume includes 12 chapters of pilgrim studies on European pilgrimages in the Catholic tradition in multidisciplinary perspectives. The contributions' methodological perspectives range from quantitative approaches of social science to qualitative approaches of the humanities, from religious studies to political science, and from philosophy to geography. The themes of this contribution reflect on the Italian landscape of pilgrimage, on the Oberammergau passion play, on the pilgrim aspect of the 1989 revolution in Romania, and two types of pilgrimage in the Catholic tradition and how they present themselves on the internet. Three social science chapters provide new data and analysis to the most popular pilgrim destination in Europe: The Ways of St. James to Santiago de Compostela. Five studies discuss papal pilgrims and pilgrim popes. The chapters range from a historical analysis of the pilgrimage from Mexico to Rome in the 19th century and a quantitative analysis of all papal addresses in Fatima in the 20th and 21st centuries, from two chapters on the most influential pilgrim pope, John Paul II, to his homeland Poland, and to an analysis of the Vatican's virtual approach to pilgrimage.